Micrographic parameters of primary stem, flower, fruit, and seed of Terminalia australis - Castro, María Teresa (2005)
Terminalia australis Cambess (Combretaceae), known as palo amarillo, is an arboreal species, less frequently shrubby, and native of Brazil, Paraguay, Uruguay, and Argentina. Antimicrobial activity was verified through investigations carried out with aqueous extracts from leaves. The purpose of the current work is to study the exo-endomorphology of the aerial organs (primary stem, flower, fruit, and seed) of the mentioned species in order to establish micrographic parameters for a future pharmacopeic monograph. Fresh and dry materials were studied. Sections and macerations were obtained. Designs were obtained with light microscope equipped with a drawing tube, and photomicrographs were generated with scanning electron microscope. Numerical values were determined: lineal magnitude for the species that are presented together with the data typical of the histoanatomy of the aerial organs.